Ethical and Methodological Considerations for Evaluating Participant Views on Alzheimer's and Dementia Research. (February 2021) - Benson, Clark; Friz, Amanda; Mullen, Shannon; Block, Laura; Gilmore-Bykovskyi, Andrea
The urgent need to expand enrollment in Alzheimer's disease and related dementia (ADRD) research has synergized calls for an empiric science of research recruitment, yet, progress in this area is hindered by challenges to measuring views toward ADRD research. This paper reports ethical and methodological considerations identified through a prospective qualitative study investigating ADRD patient and caregiver views on research recruitment and participation surrounding acute illness. Ethical and methodological considerations were identified through a combination of memoing, collaboration with a Community Advisory Board (CAB), and analysis of interview data from ADRD patients ( N = 3) and/or caregivers ( N = 28). These included risk for undue influence attributable to role ambiguity/motivational misconceptions, divergent decision-making preferences, bias contributing to low referrals of ADRD participants, and difficulty answering abstract/hypothetical questions. Many considerations were successfully addressed with multifaceted, proactive strategies, and CAB input. Findings have implications for recruitment science research and the validity of inferences regarding research preferences.